Digital strategy - Turuk, Mladen (Array, 2020)
The digital strategy presents a framework for digital business transformation and an inevitable requirement for achieving success in a digital world. The pace of change and innovation in digital businesses is not slowing down and today almost no business can ignore its digital aspect but what drives digital transformation is a strategy, not technology. Therefore, the ability to digitally reimagine the business is determined by a clear digital strategy, and the leaders able to implement it in the organization. Inertia is not the solution to uncertainty. Having a clear vision, goals and objectives help organizations to reduce this ambiguity and adapt to an everchanging digital environment. Agile outperforms the traditional approach and new, innovative organizations replace incumbents that do not adapt fast enough in a process known as creative destruction.